Kuda kepang the traditional performing art: a study case on Johor kuda kepang's motif and shapes / Nur Syafiqah Mohd Herman Cher - Mohd Herman Cher, Nur Syafiqah (2014)
Kuda Kepang also known as kuda lumping or jaran kepang is a traditional Javanese dance depicting a group of horsemen. The Kuda Kepang is a very interesting dance from Johor, The dance was once a form oftotemic worship. The dance had strong links with spirit possession andoften dancers went into a trancelike state. However with the Islamisation of Malaysia, this dance now generally renders the tale of nine Javanese men who spread the-Islamic faith in the interior ofJava. The nine Muslim evangelists rode on horseback and dramatized stories of the battles waged and won for the cause of Islam to draw and hold the attention of the congregation. Kuda Kepang is performed by nine dancers who are seated astride a two dimensional 'horse' made of hide or pleated rattan. The dancers-reenact the early Islamic battles in enthusiastic gestures and vigorous action. Naturally as time as moved this dance is seen very much more for its entertainment value. This dance is performed in accompaniment to a rich and exotic rendition of traditional music played with indigenous instruments such as gongs, tambourines and angklungs. The horse 'w ere exclusively made from bamboo arid decorated with colourful paints and cloth. These shown how creative our ancestor are. This dance started in Javanese, Indonesia but with the immigrants from Javanese to Malaysia made Malaysia have this dance too